Maternal Allostatic Load as a Predictor of Adverse Pregnancy Outcomes and Offspring Development in the F3 Generation: Evidence from a Rat Model of Transgenerational and Multigenerational Stress - Reynolds, Teddi A.; Ambeskovic, Mirela; Falkenberg, Erin A.; Awosoga, Oluwagbohunmi A.; Metz, Gerlinde A.S. (Archives of Clinical and Biomedical Research, 2024)
Clinical studies suggest that cumulative maternal stress and high allostatic load are associated with higher risk of developmental and psychophysiological disorders in the offspring. Here, we adopted the clinical concept of allostatic load to a rat model of trans- and multigenerational stress. We developed an index of maternal allostatic load as a predictive tool for adverse pregnancy and offspring health outcomes. The new maternal stress index (MSI) was used to quantify sexspecific cumulative impacts of ancestral stress across four generations. F2 mothers born to a lineage of maternal transgenerational prenatal stress (TPS) or multigenerational prenatal stress (MPS) and their F3 offspring underwent physiological and behavioural assessments. Ancestral stress altered pregnancy outcomes, with higher fetal resorption following TPS and slower pregnancy weight gain following MPS. Male and female F3 TPS offspring showed impaired sensorimotor development at postnatal day (P) 9, while only males displayed increased anxiety-like behaviours at P15. Adult F3 TPS and MPS females showed heightened behavioural and physiological stress responses. Moreover, ancestral stress altered mineral deposition in hair, reflecting dysregulated Na/K metabolism. The TPS lineage displayed the largest impact of stress with age-specific sex differences. High MSI scores served as robust indicators of maternal corticosterone, glucose and gestational weight gain. MSI scores also predicted anxiety-like behaviours in adult male but not female offspring. Thus, the MSI may provide a useful indicator of the cumulative physiological burden of maternal stress. Tools like the MSI may facilitate knowledge translation from preclinical models to human populations and back.